Community-Based Disaster Management in Yogyakarta City: Risk Analysis, Local Capacity, and Community Resilience Strategies - Usriya Fara Nabila; Moh. Ja’far Sodiq Maksum (Lembaga Institute Development of Social Economic Cociety, 2025)
This study analyzes the implementation of community-based disaster management (CBDM) in Yogyakarta City as a strategy to strengthen community resilience against flood and earthquake risks. The research employs a qualitative descriptive approach through literature review and secondary data analysis drawn from official documents, statistical data, and regional disaster risk assessments. The findings reveal that disaster risks are influenced by population density, weak drainage systems, and low public awareness of mitigation. However, Yogyakarta’s communities possess strong social and cultural capital—such as gotong royong (cooperation), tepo seliro (empathy), and ilmu titen (local observational knowledge)—which can be integrated with modern technology. Lessons from Japan and the Philippines highlight the importance of community participation and institutional support in disaster risk reduction. This study recommends strengthening community institutions, expanding disaster education, and integrating local wisdom into mitigation systems to realize a resilient, community-based disaster management model.